Encyclopedia of adventure fiction [ - D'Ammassa, Don , 1946- (Gale virtual reference library, 2009)
"Stories replete with danger, action, and unusual events have been beloved by readers from ancient times to the present day. The new Encyclopedia of Aduenture Fiction covers the very best of this genre, from literary classics such as Charles Dickens's A Tale of Two Cities and Joseph Conrad's The Secret Agent to tales that have enthralled younger readers for many years, such as Treasure Island and The Wizard of Oz, to the finest of today's best-selling adventure stories."-- Jacket